Attitudes of nurses in Greece towards influenza vaccination - Raftopoulos, Vasilios (My University, 2008)
AIM: To explore the knowledge, attitudes and beliefs of nurses in Greece towards influenza vaccination. METHOD: Four focus groups were conducted with 30 nurses. Content analysis of the focus group interviews was undertaken. FINDINGS: Participants were knowledgeable about influenza and the influenza vaccination. The main reasons given for not being vaccinated were: being in good health, not being susceptible to influenza, thinking it was not needed, concern about its effectiveness, delayed availability and distribution of influenza vaccines, fear of vaccine-induced illness, and lack of support regarding the provision of information on the benefits of influenza immunisation. CONCLUSION: Targeted health education programmes should be developed to overcome misconceptions about influenza vaccination.
Keywords: Nursing care; Nursing--Greece